Open and Equal Access for Learning in School Management - Altınay, Fahriye (IntechOpen, 2018)
This book encapsulates four sections about open and equal access for learning in school management. The first section is related to school management and leadership. Second section of the book gives insight on school culture. Third section of the book underlines the importance of open learning. Latest section of the book covers the importance of equal acess and learning in curriculum, environment, gender, youth. I have a firm belief that authors can find great insights on open and equal access for learning from different reflections and researches of chapters.